Gender differences in provider practice characteristics and medicare payment & services among diagnostic radiologists - Ajay Malhotra; Chris J. Lee; Mihir Khunte; Raj Moily; Dheeman Futela; Seyedmehdi Payabvash; David Seidenwurm; Dheeraj Gandhi (PLoS ONE, 2026)
Background Gender-based differences in representation, practice settings, sub-specialty, billings, and payments among radiologists are poorly understood. Purpose To compare representation, scope of practice, productivity, and Medicare payments between female and male diagnostic radiologists. Methods and materials This cross-sectional (2017–2021) retrospective study examined the CMS Medicare Fee-for-Service Provider Utilization and Payment Database for payments to male and female diagnostic radiologists. The study practice setting, volume of services provided, number of unique beneficiaries served and financial data. Descriptive statistics were reported as mean with standard error (SE) for financial variables and median with interquartile range (IQR) for non-financial variables. Results Between 2017–2021 data, a total of 33,029 diagnostic radiologists provided services to Medicare fee-for-service beneficiaries, of whom 8,217 (24.9%) were female. Female radiologists were disproportionately in academic versus non-academic radiology (34.2% vs 22.6%); practicing in urban versus rural areas (26.3% vs 17.0%); in larger practices (30.1% in practices with ≥100 radiologists vs 17.5% in practices with 1–9 radiologists); and in certain subspecialties (breast imaging- 64.9%). On average, female radiologists received 86% of the total Medicare payments received by male radiologists (mean [SE], $301,931 [$1810] vs $352,604 [$1,164]; p < .001). Female radiologists billed fewer median total services (6,660 vs 9,859; p < .001), served fewer beneficiaries (5,441 vs 7,678; p < .001), and billed fewer unique codes (20 vs 39; p < .001). Overall, female radiologists’ average (SE) payment per service was 18% higher than males [$36.26 (0.13) versus $30.71 (0.06), respectively, but were similar within each subspecialty. Conclusion Female radiologists are disproportionately in academic, urban, and large practices and work as subspecialists. Further, while total Medicare payments received by females were less than males, average payments per service were higher for females overall, but comparable by sex in the same subspecialty.